ASPECTS SOCIO-ECONOMIQUES DES EMBALLAGES-FEUILLES DES ZONES HUMIDES DU SUD BENIN - Gbesso G. H. François; Gbesso Florence K.; Gbaguidi S. L. Marcelle (European Scientific Journal, ESJ, 2015)
The present study on the socio-economic importance of the vegetable packing-sheets of the wetlands took place in three townships (AbomeyCalavi, Cotonou and Porto-Novo). It mainly aims at evaluating the potential of the area in vegetable species used as traditional packing by local people and their socio-economic importance for a better use of these species. Socioeconomic surveys were directed towards 270 sellers /users of the sheets like packing. The availability, the economic and ethnobotanic practical values of the species were given. Tests of comparison were carried out between different socio-demographic categories for the use of these species. Ten (10) species divided into ten (10) genres and families were listed. Thalia geniculata (85%), Lasimorpha senegalensis (45%), Tectona grandis (35%) and Musa sp (30%) are the most species used by the populations. The use of packing vegetable sheets depends on the educational level and the monthly income of respondents. These sheets make object of a flourishing trade paying of the substantial incomes (5000 to 8000FCFA/ day) to the sales women. This study could made up a data base for a better use of these species of biodegradable sheets for the environmental protection.